1992
DOI: 10.1677/jme.0.0090103
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide in the eel, Anguilla anguilla L.: its cardiac distribution, receptors and actions on isolated branchial cells

Abstract: The presence of atrial natriuretic peptide (ANP) and the nature of its binding sites were studied in fresh-water (FW)- and seawater (SW)-adapted eels using a heterologous analogue, that of the rat (rANP). Rat ANP-like immunoreactivity was demonstrated in the cardiac atria and ventricles of both FW and SW eels, and electron-dense ANP-like granules were observed. The atria and ventricles of FW eels contained significantly more granules than those of SW animals and, in both types, the atria were more granular tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Since eel gills contain large amounts of NPR-C and/or NPR-D (Sakaguchi et al 1993, it is possible that the Scatchard analysis could not detect a small quantity of the CNP-specific NPR-Bs, which are present in the chloride cells of FW-adapted eels. By contrast, Broadhead et al (1992) demonstrated two classes of receptor in chloride cell-enriched gill cells of SW-adapted Anguilla anguilla using rat 125 I-ANP, but only one class was detected in those of FW-adapted eels. The reason for the difference between A. anguilla and A. japonica is not known at present.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Since eel gills contain large amounts of NPR-C and/or NPR-D (Sakaguchi et al 1993, it is possible that the Scatchard analysis could not detect a small quantity of the CNP-specific NPR-Bs, which are present in the chloride cells of FW-adapted eels. By contrast, Broadhead et al (1992) demonstrated two classes of receptor in chloride cell-enriched gill cells of SW-adapted Anguilla anguilla using rat 125 I-ANP, but only one class was detected in those of FW-adapted eels. The reason for the difference between A. anguilla and A. japonica is not known at present.…”
Section: Discussionmentioning
confidence: 71%
“…The possible roles of ANP in osmoregulation have been described in the eel by Takei & Balment (1993). ANP receptors in eel gill cells have previously been examined using rat 125 I-ANP (Broadhead et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A N P than atria, con firms results from morphometric and biosynthetic studies on other fish species (Baranowski and Westenfelder 1989). Because we used a heterolo gous R IA , we cannot compare our data directly with other studies on fish, in which a variety of homologous and heterologous antisera was used (Baranowski and Westenfelder 1989;Evans et al 1989;Evans 1990;Broadhead et al 1992;Powell and Miller 1992;Takei et al 1992). Most likely, our antiserum recognized both A N P and VNP (Takei et al 1992).…”
Section: A C T H and Seawater Adaptationmentioning
confidence: 95%
“…Clearly, additional work is warranted using multiple fish species comparing the actions of (Katafuchi et al 1994). Furthermore, receptor profiles for atrial natriuretic peptide in the gills, another target tissue for A N P, varies between FW-and SW-adapted eels (Broadhead et al 1992). …”
Section: A C T H and Seawater Adaptationmentioning
confidence: 99%